Characterization of hepatitis C virus replication in cloned cells obtained from a human T-cell leukemia virus type 1-infected cell line, MT-2. - Mizutani, T (1996)
We recently found that a human T-cell leukemia virus type 1-infected cell line, MT-2, could support the replication of hepatitis C virus (HCV) (N. Kato, T. Nakazawa, T. Mizutani, and K. Shimotohno, Biochem. Biophys. Res. Commun. 206:863-869, 1995). In order to develop a culture system in which HCV replicates more efficiently, we examined the efficiency of HCV replication in cloned MT-2 cell lines by the limiting dilution method. Consequently, we obtained five clones in which intracellular positive-stranded HCV RNA could be detected until at least 21 days postinoculation (p.i.), as opposed to 15 days p.i. in uncloned MT-2 cells. MT-2C, one of the five clones which supported HCV replication up to 30 days p.i., was used for further characterization of HCV replication. Semiquantitative analysis of HCV by PCR revealed that RNA synthesis in infected cells increased after inoculation, reached a maximum level at 4 days p.i., and maintained this level until at least 11 days p.i. The 5' untranslated region of negative-stranded HCV RNA was also detected in the infected cells by two different methods with strand specificity. These results suggest that HCV replicated and multiplied in the MT-2C cells. HCV-infected MT-2C cells that were treated with antibiotics, such as G418 and hygromycin B, sustained HCV RNA for a longer period than did untreated cells. We demonstrated inhibitory effects on HCV replication by an antisense oligonucleotide complementary to the HCV core encoding region and by interferon-alpha. Furthermore, cell-free viral transmission was demonstrated by this culture system. These results suggest that our cell culture system will be useful for studying the mechanism of HCV replication, for screening antiviral agents, and for developing HCV vaccines.